Interaction of ⅠL-17A (rs2275913-G/A) and ⅠL-17F (rs763780 T/C) Gene variants with acne vulgaris - A. Ennad, Abbas; M. Khadhim, Manal (Medicinski časopis, 2023)
Background: Acne vulgaris is a prevalent dermatological disorder that affects pilosebaceous units and has a complex aetiology, it reveals inflammatory and non-inflammatory skin disorders. Aim: The purpose of the current study is to evaluate the expression of IL-17A and IL-17F gene polymorphism in patients with acne vulgaris and their relationship to the severity of the condition. Methods: The study comprised sixty patients suffering from Acne vulgaris who were consulted to the dermatological section from the period November /2022 – march/ 2023 whereas the second category consisted of sixty individuals assumed to be healthy who served as a control. Results: The correlation between IL-17A (rs2275913-G/A) gene polymorphism and acne vulgaris disease reveals no significant difference between patients category and control category (p > 0.05) in all codominance and recessive mode, but according to the risk factor of the AA and G/A genotypes can be considered as a risk factor (OR =2.77 and 2.19) respectively with etiological fraction (EF=0.346 and 0.331). Regarding the genotypes and alleles frequencies concerning IL-17F (rs763780 T/C)  SNP, there was no significant statistical distinction between the two groups (p= 0.275). But the risk investigation indicated that the CC and T/C genotypes may be considered as risk factors and etiological fractions for the acne vulgaris (OR= 3.42; OR of 1.37) respectively. Conclusion: AA and G/A genotypes in IL-17A as well as  CC and T/C genotypes in IL-17F may be a risk factor for acne vulgaris.
Keywords: Acne vulgaris; IL-17A; IL-17F; Gene polymorphism; ARMS-PCR